2006
DOI: 10.1021/ma061054h
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bisphenol Monomer with Grafting Capability and the Resulting Poly(arylene ether sulfone)s

Abstract: A novel bisphenol monomer with grafting capability and the resulting poly(arylene ether sulfone)s Li, Z.; Ding, J.; Robertson, G.P.; Guiver, M.D. ABSTRACT: A new bisphenol monomer, 1,1-bis(4-hydroxyphenyl)-1-(4-(4-fluorophenyl)thio)phenyl-2,2,2-trifluoroethane (3FBPT), containing a masked grafting site was readily synthesized in high yield in two reaction steps. A conventional aromatic nucleophilic substitution (S N Ar) was used for copolymerization of this monomer with difluorodiphenyl sulfone and hexafluorob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…High cost, synthetic difficulty, toxic intermediates, loss of proton conductivity at high temperatures (>100°C), and high methanol crossover are serious drawback for practical applications in fuel cells. Therefore, there has been a great deal of research in the development of alternative proton conducting membranes to the perfluorinated membranes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…High cost, synthetic difficulty, toxic intermediates, loss of proton conductivity at high temperatures (>100°C), and high methanol crossover are serious drawback for practical applications in fuel cells. Therefore, there has been a great deal of research in the development of alternative proton conducting membranes to the perfluorinated membranes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…They found that SPI with sulfonic groups introduced to flexible aliphatic side chains, the proton conduction activation energy (E a ) was smaller than that of SPI with sulfonic groups directly attached to main chain. Some studies about sulfonated poly(arylene ether)s with sulfonic groups introduced to side chains have been also reported in recent years [22][23][24][25][26][27][28]. Most of them were obtained by graft or post-sulfonation process to introduce sulfonated group to polymer side chain, while direct copolymerization method was seldom adopted due to the limitation of sulfonated monomers.…”
Section: Introductionmentioning
confidence: 99%
“…sulfonated poly(arylene ether)s with sulfonic groups introduced onto side chains have also been reported in later years. [22][23][24][25][26][27][28][29] Most of the polymers were obtained by a graft or post-sulfonation process to introduce the sulfonated group to the polymer side chain. Compared to chemical grafting and post-sulfonation methods, the direct copolymerization method allows close control of the polymer structure, which includes the sulfonate content (SC) in the polymer.…”
Section: Introductionmentioning
confidence: 99%